Educating parents on ‘speaking up for hand hygiene’ in PICU: perceptions and barriers - Mohd Ali, Noor Azizah; Jauncey-Cooke, Jacqueline; Ballard, Emma L; Bogossian, Fiona (IIUM Press, 2021)
Background: Hand hygiene is fundamental approach to prevent and control spread of infection. Many measures available to enhance compliance to hand hygiene, yet little is known of ‘speaking up for hand hygiene’ initiative among parents and nurses especially in paediatric intensive care unit (PICU). Aim: To assess parents’ and nurses’ perceptions on ‘speaking up for hand hygiene’ in the prevention of ventilator-associated pneumonia (VAP) in a PICU. Methods: We revised evidence-based information related to VAP preventative strategies for a PICU population and updated education materials for staff and families using the ‘Speaking up for Hand Hygiene’ initiative. Parents of children receiving mechanical ventilation were provided with education on hand hygiene. Parents and staff groups were invited to participate in a survey exploring their confidence with this initiative. Results: Parents (78.9%) and nurses (91.2%) agreed the initiative would increase hand hygiene practice. Parents (94.5%) would welcome being reminded about hand hygiene but only 68.4% of parents were willing to remind nurses and 78.9% to remind other PICU staff. Nurses (88.2%) reported being willing to remind parents and other PICU staff and 88.2% indicated that they would welcome being reminded about hand hygiene from parents and 94.1% from other PICU staff. Conclusion: Parents of children receiving mechanical ventilation and PICU nursing staff perceived ‘Speaking up for hand hygiene’ as an important initiative. There are, however factors that contribute to a reluctance to prompt hand hygiene that require further research.